An Examination of the Relationship of the 16PF Fifth Edition to a Multidimensional Model of Self-Esteem - Pietrzak, Dale; Page, Betsy; Korcuska, James S.; Bach Gorman, Amber (SAGE open, 2015)
The regression equation needed to predict the self-esteem score from the Sixteen Personality Factor Questionnaire (16PF) Fifth Edition is not available for hand scoring. This score is derived from the Coopersmith’s Self-Esteem Inventory (SEI), which is based on a unitary model of self-esteem. The SEI may be subject to gender and extroversion biases. Moreover, there is a gap in the literature on the 16PF fifth edition and self-esteem. For these reasons, we investigated the relationship of the Culture-Free Self-Esteem Inventory–II Form AD (CFSEI-II), a multidimensional model of self-esteem, using multiple regression to the scales of the 16PF. Based on the adult sample of 234 in this study, we developed and made available to users of the 16PF split sample–validated regression equations for this multidimensional model of self-esteem.